Circannual rhythm of plasmatic vitamin D levels and the association with markers of psychophysical stress in a cohort of Italian professional soccer players. (21st April 2017) - Lombardi, Giovanni; Vitale, Jacopo Antonino; Logoluso, Sergio; Logoluso, Giovanni; Cocco, Nino; Cocco, Giulio; Cocco, Antonino; Banfi, Giuseppe
ABSTRACT: Adequate plasmatic Vitamin D levels are crucial to maintain calcium homeostasis and bone metabolism both in the general population and in athletes. Correct dietary supply and a regular sun exposure are fundamental for allowing the desired and effective fitness level. Past studies highlighted a scenario of Vitamin D insufficiency among professional soccer players in several countries, especially in North Europe, whilst a real deficiency in athletes is rare. The typical seasonal fluctuations of Vitamin D are wrongly described transversally in athletes belonging to teams that play at different latitudes and a chronobiologic approach studying the Vitamin D circannual rhythm in soccer players has not been described yet. Therefore, we studied plasma vitamin D, cortisol, testosterone, and creatin kinase (CK) concentrations in three different Italian professional teams training at the same latitude during a period of two consecutive competitive seasons (2013 and 2014). In this retrospective observational study, 167 professional soccer players were recruited (mean age at sampling 25.1 ± 4.7 years) and a total of 667 blood drawings were carried out to determine plasma 25(OH)D, serum cortisol, serum testosterone and CK levels. Testosterone to cortisol ratio (TC) was calculated based as a surrogate marker of overtraining and psychophysical stress and each athlete was drawn until a maximum of 5 times per season. Data extracted by a subgroup of players that underwent at least 4 sample drawings along a year ( N = 45) were processed with the single and population mean cosinor tests to evaluate the presence of circannual rhythms: the amplitude (A), acrophase (Φ) and the MESOR (M) are described. In total, 55 players (32.9%) had an insufficient level of 25(OH)D during the seasons and other 15 athletes (9.0%) showed, at least once, a deficiency status of Vitamin D. The rhythmometric analyses applied to the data of Vitamin D revealed the presence of a significant circannual rhythm ( p < 0.001) with the acrophase that occurred in August; the rhythms of Vitamin D levels were not different neither among the three soccer teams nor between competitive seasons. Cortisol, testosterone and TC showed significant circannual rhythms ( p < 0.001): cortisol registered an acrophase during winter (February) while testosterone and TC registered their peaks in the summer months (July). On the contrary, CK did not display any seasonal fluctuations. In addition, we observed weak but significant correlations between 25(OH)D versus testosterone ( r = 0.29 and p < 0.001), cortisol ( r = −0.27 and p < 0.001) and TC ( r = 0.37 and p < 0.001). No correlation was detected between Vitamin D and CK. In conclusion, the correct chronobiologic approach in the study of annual variations of Vitamin D, cortisol and testosterone could be decisive in the development of more specific supplementation and injury prevention strategies by athletic trainers and physicians.